Comparison of O–H and C–H activation of methanol on Ni-based cluster: a DFT investigation. (17th June 2020) - Lian, Xin; Guo, Wenlong; He, Bai; Lin, Yingxi; Xu, Peng; Yi, Huan; Chen, Shuangkou
Abstract : Using the density functional theory, the initial dehydrogenation of methanol on Nix My (M = Ni, Co, Fe, Mn, Cr, x  +  y  = 4, y  = 1, 2) clusters is investigated. Two adsorption and dehydrogenation mechanisms of methanol are studied: one proceeds along the C–H scission and another begins with the breaking of the O-H bond. The adsorption sites of methanol on the Ni or M sites of the Nix My clusters are considered. The adsorption of methanol on Ni4 cluster is stronger than those on bimetallic clusters, while the initial dehydrogenation barriers on Nix My clusters are lower than that on Ni4 cluster. The comparable energy barriers of two pathways (O–H or C–H dissociation) on Ni-based clusters indicate that these two paths are quite competitive. In addition, the Ni2 M2 clusters show superior activation performance compared with the Ni3 M clusters, especially for Ni2 Mn2 and Ni2 Cr2 clusters. The effects of alloyed metal on the catalytic activity of Ni for methanol initial dehydrogenation, including the adsorption energy, O–H or C–H bond scission barrier and frontier molecular orbital levels, are discussed. It can be concluded that the addition of Co, Fe, Mn and Cr to Ni catalyst is able to enhance the activity of the methanol dehydrogenation reaction. GRAPHICAL ABSTRACT: